The launch of the ESPEN Special Interest Group in Paediatric Clinical Nutrition. (June 2017) - Gerasimidis, K.; Hulst, J.M.; Chourdakis, M.; Huysentruyt, K.; Koletzko, B.; Joosten, K.F.M.
Summary: Background & aims: At the 37th annual ESPEN congress in Lisbon, a new Special Interest Group (SIG) in Paediatric Clinical Nutrition was formed. As a first activity of this group, a survey was sent out to all ESPEN members to collect opinions about the objectives of this SIG, explore the interest of ESPEN members in paediatric related nutrition research and clinical practice and to offer to the opportunity for a wider future participation. Methods: A web-based questionnaire survey was distributed to all members of ESPEN via the regular society's newsletter. Results: In total, 123/2828 (4.3%) ESPEN members from 50 countries completed the survey. Fifty-nine of the responders were working in paediatric clinical practice and/or research, 42 in adult medicine, and 20 in both. Fifty-seven (51%) respondents agreed that there is inadequate representation of paediatric nutrition in the current ESPEN activities and 90% of all would like to see more paediatric topics at the ESPEN annual congresses. The development of paediatric clinical practice guidelines should be the scope of this SIG, as indicated by 85 (69%) respondents. Seventy-six (69%) believed that the creation of a Paediatric Clinical Nutrition SIG is likely to impact positively on the society's membership. Conclusions: There is an unmet need for more paediatric related topics and representation with the activities of the ESPEN group. The SIG in Paediatrics aspires to foster multicentre research, development of guidelines and provide a hub for interaction and knowledge exchange.